Three-dimensional thermal fracture analysis of a one-dimensional hexagonal quasicrystal coating with interface cracks - Zhang, X.; Fan, C.Y.; Lu, Chunsheng; Zhao, M.H.; Dang, H.Y. (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
On the basis of displacement and temperature discontinuity boundaries, the three-dimensional fracture behavior of an interface crack is investigated in a one-dimensional hexagonal quasicrystal coating under thermal–mechanical loads. The Hankel transform technique is firstly adopted to derive the fundamental solutions for interfacial displacement and temperature discontinuities, and the corresponding boundary integral–differential equations are constructed. Next, Green's functions with uniform discontinuities over a ring element are derived, and a boundary element method is proposed. Then, stress intensity factors and the energy release rate are given in terms of displacement discontinuities. Finally, the effects of material mismatch, coating thickness, crack size and applied loads on the fracture behavior are briefly discussed through numerical case studies.